2019
DOI: 10.1002/ccd.28144
|View full text |Cite
|
Sign up to set email alerts
|

One‐year clinical outcome with a novel self‐expanding transcatheter heart valve

Abstract: ObjectivesTo evaluate 1‐year outcome using the ACURATE neo (Symetis S.A., a Boston Scientific Company, Ecublens, Switzerland) according to the updated Valve Academic Research Consortium (VARC‐2) with emphasis on the composite endpoints “clinical efficacy after 30 days” and “time‐related valve safety”.BackgroundInitial reports on the clinical performance of patients treated with the ACURATE neo are promising; however, information regarding one‐year outcome is scarce, especially with regard to the composite endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 38 publications
(65 reference statements)
3
25
0
Order By: Relevance
“…The lower radial force may lead to less mechanical injury to the conduction system (Fig. 1 ) and explain the relatively low need for a new permanent pacemaker ranging from 8.3 to 12.3% [ 10 12 , 13 •, 15 , 16 , 17 •], which is considerably lower than reported pacemaker rates of other self-expanding THVs (17.4 to 34.1%) [ 3 , 21 ]. Evidence from a small multicenter study suggested that the rate of new permanent pacemakers can be reduced to 2.3% when applying a minimizing trauma strategy using a smaller balloon for pre- and post-dilation [ 12 ].…”
Section: The Acurate Neo Device For Native Aortic Valve Stenosismentioning
confidence: 99%
See 3 more Smart Citations
“…The lower radial force may lead to less mechanical injury to the conduction system (Fig. 1 ) and explain the relatively low need for a new permanent pacemaker ranging from 8.3 to 12.3% [ 10 12 , 13 •, 15 , 16 , 17 •], which is considerably lower than reported pacemaker rates of other self-expanding THVs (17.4 to 34.1%) [ 3 , 21 ]. Evidence from a small multicenter study suggested that the rate of new permanent pacemakers can be reduced to 2.3% when applying a minimizing trauma strategy using a smaller balloon for pre- and post-dilation [ 12 ].…”
Section: The Acurate Neo Device For Native Aortic Valve Stenosismentioning
confidence: 99%
“…Several studies have investigated the clinical outcomes up to 1 year after implantation of the ACURATE neo THV for treatment of severe aortic stenosis in elderly patients (Table 1 ) [ 10 12 , 13 •, 14 •, 15 , 16 , 17 •, 18 •, 19 , 20 ]. These studies have proposed some strengths and drawbacks of ACURATE neo, which may guide how to optimally tailor the device to the most appropriate anatomy.…”
Section: The Acurate Neo Device For Native Aortic Valve Stenosismentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of the journal, Pellergrini and colleagues publish their single center VARC‐2 defined 1 year outcomes with a novel self‐expanding THV, the ACURATE neo (Symetis/Boston Scientific, Ecublens, Switzerland) in a population of intermediate risk patients (median logistic Euroscore I = 13.8). The ACURATE neo is a second generation Nitinol self‐expanding, supra annular porcine pericardial tissue THV.…”
mentioning
confidence: 99%